في أنشطة التعليم العالي العربيQuality Assurance منطلقات ضمان الجودة - د. ميسر ابراهيم احمد; ليلى مصطفى محمـد (PROSPECTIVE RESEARCHES, 2023)
The sixteenth of the past century witnessed inclination of many quality concepts which are on the prevention philosophy and not on the remedial as a re-active approach to quality management in productive and service activities. With the increase of competition, productive and service organizations adopt these concepts to cope with the new changes and the client's satisfaction. Different concepts for the quality have been used in service activities, especially in Higher Education to ensure quality setups in the basic system of education and it's environment (the process of education, the faculty, the students and the curriculum). This paper attempts to derive these concepts to Arabian Higher Education activities through building a comprehensive frame in Higher Education processes after indicating a limited concern to quality concepts in most of the Arab Higher Education Organizations. The research comes up with a number of results that promote and avail quality assurance concept in Higher Education activities after it has provided a model which sets out the systematic approach in building the mechanism of implementation.